Prevention and Eradication of Drug Abuse and Illicit Trafficking Among Students by National Narcotics Board of Purbalingga Regency: An Efforts to Achieve Substantive Justice - Abdiyono, Pamuji; Susanti, Rahtami; Saefudin, Yusuf (Universitas Muhammadiyah Sumatera Utara, 2025)
Narcotics and illegal drugs have become a real threat that can destroy the Indonesian Nation. The problems of drugs has become one of the problems that has long required serious handling. The implementation of the program to prevent and eradicate drug abuse and illicit trafficking among students is one of the important efforts in realizing substantive justice. This research uses an empirical research method with a qualitative approach. Data were collected through interviews and observations with National Narcotics Board of Purbalingga Regency, Pratama Clinic National Narcotics Board of Purbalingga Regency, Nurul Ichsan AL-Islami Rehabilitation Center, teacher, and students, as well as analysis of related documents. The results showed that National Narcotics Board of Purbalingga Regency has made various efforts to implement the program among students, by conducting socialization in schools. There are several challenges in implementing this program, such as lack of human resources, budget, and geographical location. The implementation of the prevention and eradication of drug abuse and illicit trafficking among students by National Narcotics Board of Purbalingga Regency has contributed to increasing students’ awareness and knowledge about the dangers of drugs.